2007
DOI: 10.1002/pbc.20883
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment outcomes of childhood Hodgkin lymphoma in two US centers and a center in Recife, Brazil

Abstract: Intensive frontline therapy should be considered for patients with unfavorable HL in LIC where the relapse rate is high and the salvage rate is low, provided that supportive care is adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
(20 reference statements)
1
21
0
3
Order By: Relevance
“…Using a similar treatment strategy, Hsu et al have shown a significant difference in the outcome of children treated in a low income country compared with centers in the US [22]. The authors did not comment on the possible reasons for the increased failure rate.…”
Section: Discussionmentioning
confidence: 94%
“…Using a similar treatment strategy, Hsu et al have shown a significant difference in the outcome of children treated in a low income country compared with centers in the US [22]. The authors did not comment on the possible reasons for the increased failure rate.…”
Section: Discussionmentioning
confidence: 94%
“…When seen, younger children have a higher incidence of lymphocyte-predominant and mixed cellularity histology and a lower incidence of nodular sclerosing histology than adolescents and adults [1,10Á23]. The study by Hsu et al [22] compared the epidemiology of HL in both developed and developing countries. The median age in developing countries (9 years) was lower than in developed countries (15.3 years).…”
Section: Discussionmentioning
confidence: 99%
“…With this combined modality treatment, survival is achieved in up to 90% of patients with HL [1]. In developed countries, OS rates were reported to be 89.3Á100% [10,17,22]. Low-dose involved field radiotherapy was successful in the COG study [16], which stratified patients according to disease stage and patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…28,[33][34][35] In some cases adjustment of the chemotherapy regimen will be required to maximize the probability of cure; in all cases, improvements in supportive care and efforts to reduce abandonment will be required. 35 A hospital-based cancer registry and active data management program are essential to successfully monitor outcomes and measure the effect of specific interventions.…”
Section: Retinoblastomamentioning
confidence: 99%
“…Geographic differences in incidence may suggest unique genetic or environmental exposures that affect cancer risk. In this report we review the inci- Health planning Measurement of the geographic distribution and total number of cases of each cancer type allows planning of the location where pediatric cancer units and satellite clinics should be established and determination of services needed at each site Honduras satellite clinics; development of a regional flow cytometry center 45 Quality improvement Measuring outcomes of treatment and cancer-specific mortality identifies services that need to be improved and facilitates assessment of the efficacy of interventions Development of a pediatric cancer center of excellence in Recife, Brazil 34 Clinical research Adaptation of pediatric oncology treatment regimens Conducting clinical trials of therapy in LIC that use less toxic, less expensive, or otherwise modified versions of published treatment regimens can evaluate the feasibility and outcomes in the local setting ALL and lymphoma in Recife, Brazil, 33,34 Indonesia, 35 and India [46][47][48] Clinical research that can only be performed in LIC Evaluation of clinical problems unique to children with cancer in LIC, including abandonment of therapy, the effects of extreme poverty on compliance and toxicity, and the effects of comorbid illnesses (e.g. malnutrition, parasitic infection) on outcomes can lead to specific mitigation strategies Abandonment risk factors for children with ALL 23,34,35 ; telemedicine in Jordan to improve treatment of central nervous system cancer 49 Comparative clinical research Evaluation of specific aspects of care in diverse settings, such as the effects on outcome of culture, language, socioeconomic status, and other variables that differ greatly between countries…”
mentioning
confidence: 99%